Penggunaan Metode Eksperimen Berbantuan Media Konkret Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas IV SD Negeri 1 Seraya Barat - I Nengah Yusa Yusyana (Cetta: Jurnal Ilmu Pendidikan, 2021)
This study aims to improve the learning process by improving the science learning outcomes of fourth grade students of SD Negeri 1 Seraya Barat through the use of experimental methods assisted by concrete media. This classroom action research is designed in two cycles. Each cycle is carried out in four stages, namely: planning, implementation, evaluation, and reflection. The subjects of this study were fourth grade students of SD Negeri 1 Seraya Barat for the academic year 2019/2020 in the odd semester with a total of 32 students. The object of this research is the result of learning science on sound material. Science learning outcomes data were collected using the learning outcomes test. Data were collected using the test method. All data collected were analyzed descriptively. The criteria for the success of the action if the average student learning outcomes in science are at least 68 with classical mastery of at least 85%. The results showed that the use of experimental methods assisted by concrete media could improve science learning outcomes for fourth grade students of SD Negeri 1 Seraya Barat in the odd semester of the 2019/2020 school year. This can be seen from the results of the data analysis of learning outcomes which reached 78.33 with a good category in the first cycle then in the second cycle it increased by 10.21 so that it became 88.54 with a very good category. In addition, learning mastery has increased by 31.25% from 65.63% to 96.88%. Based on these results, it can be concluded that the use of experimental methods assisted by concrete media can improve science learning outcomes for fourth grade students of SD Negeri 1 Seraya Barat in the odd semester of the 2019/2020 school year.